2013
DOI: 10.1016/j.biocel.2013.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Applications of snake venom components to modulate integrin activities in cell–matrix interactions

Abstract: Snake venom proteins are broadly investigated in the different areas of life science. Direct interaction of these compounds with cells may involve a variety of mechanisms that result in diverse cellular responses leading to the activation or blocking of physiological functions of the cell. In this review, the snake venom components interacting with integrins will be characterized in context of their effect on cellular response. Currently, two major families of snake venom proteins are considered as integrin-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 126 publications
0
50
0
1
Order By: Relevance
“…The best studied venom compounds affecting neovascularization are proteins, which interact with integrins expressed on endothelial cells. These proteins serve mainly as inhibitors of angiogenesis and are members of the disintegrins family [5,6]. The most potent anti-angiogenic effect is typically attributed to disintegrins that contain an RGD motif in their active sites.…”
Section: Introductionmentioning
confidence: 99%
“…The best studied venom compounds affecting neovascularization are proteins, which interact with integrins expressed on endothelial cells. These proteins serve mainly as inhibitors of angiogenesis and are members of the disintegrins family [5,6]. The most potent anti-angiogenic effect is typically attributed to disintegrins that contain an RGD motif in their active sites.…”
Section: Introductionmentioning
confidence: 99%
“…As our targeting agent, we used Bit, a disintegrin, which specifically binds to the ligand-binding pocket of the PFR through an RGD motif. 16 The coupling methods used to covalently bind Bit to the F-NDPs apparently preserved Bit's biological activity and specificity (Figures 2-5), indicating that coupling through the carboxyl group present on the F-NDPs does not interfere with the active conformation of this disintegrin and that the integrin-binding loop which contains the RGD sequence is fully accessible to fibrinogen receptor. Therefore, Bit is an appropriate ligand to specifically bind to PFR associated with activated platelets encased in a clot.…”
Section: Discussionmentioning
confidence: 99%
“…15 Bitistatin (Bit) belongs to the family of snake venom disintegrin proteins, which contain an arginyl-glycyl-aspartic (RGD) motif in their active sites, rendering these disintegrins cross-reactive with integrins, including the platelet fibrinogen receptor (PFR), α IIb β 3 integrin. 16 A radiolabeled form of this disintegrin has been used for the detection of deep vein thrombosis in a canine model. 17,18 Data from an initial clinical trial, assessing the biodistribution of [ 99m ]Tc-labeled Bit, suggest that this disintegrin did not induce clots nor did it change the levels of circulating platelets.…”
mentioning
confidence: 99%
“…In general, the inhibition of platelet aggregation caused by disintegrins from snake venoms depends on its ability to interact with α IIb β 3 integrin (Marcinkiewicz, 2013). Investigations into this mechanism (Kauskot et al, 2008;Marcinkiewicz et al, 1997) showed that the interaction of the RGD disintegrins with α IIb β 3 integrin block the connection with fibrinogen, thereby This binding also contributes to the appearance of bleeding (Hong et al, 2003).…”
Section: Disintegrinsmentioning
confidence: 95%
“…Furthermore, it inhibits melanoma cell adhesion to fibrinogen and fibronectin, mainly by interfering with the function of α v β 3 integrin (Limam et al, 2010). However, the specific integrin-binding motif was not determined (Marcinkiewicz, 2013). In turn, leucurogin, a recombinant disintegrin-like cloned from B. leucurus, is able to inhibit platelet aggregation induced by collagen, probably through interactions with integrins α 1 β 1 or α 2 β 1 (Higuchi et al, 2011).…”
Section: Leberagin-c a Dis-likementioning
confidence: 97%